Book Review / Рецензия книг / Buchbesprechung - Anja Franz; Krisztina Sebestyén (International Dialogues on Education: Past and Present, 2015)
Renz-Polster, Herbert (2014): Die Kindheit ist unantastbar. Warum Eltern ihr Recht auf Erziehung zurückfordern müssen.